Model description of the H–bonded transuranium complexes - Stasyuk, I.V.; Ivankiv, O.L.; Velychko, O.V.; Holubets, T.V. (Condensed Matter Physics, 1999)
In the framework of conﬁgurational model it is established that regions of
existence of various forms of actinide hydroxocomplexes at variation of solution pH depend on differences of conﬁguration energies and temperature.
Saturation effect is found out, which leads to a sharp change of ligand concentration. Model of the polymerization of ionic groups UO₂[(OH)₂UO₂]²⁺ n into chain structure via hydrogen bonds is proposed. The thermodynamic
stability of such a formation is investigated depending on the number of
links at different temperatures and at various boundary conditions. В рамках конфігураційної моделі встановлено, що при зміні pH розчину області існування різних форм гідроксокомплексів залежать від
різниці конфігураційних енергій та температури. Виявлено ефект насичення, що приводить до різкої зміни концентрації лігандів. Запропоновано модель полімеризації іонних груп UO₂[(OH)₂UO₂]²⁺ n в ланцюжки через водневі зв’язки. Вивчено стійкість таких утворень залежно від числа зв’язків при різних температурах та крайових умовах.